Development of Wheatgrass (Triticum aestivum) Extract Loaded Solid Lipid Nanoparticles using Central Composite Design and its Characterization- Its In-vitro Anti-cancer Activity - Minocha, Neha; Pandey, Parijat; Sharma, Nidhi; Saini, Sangita (Current Nanomaterials, 2024)
Background: The prevalence of cancer is around the world and is identified as a multifactorial ailment. One of the most common causes of cancer in the world is oxidative stress, and this can be overcome by taking herbal plant wheatgrass in any form. As colloidal carriers with particle sizes of 50-1,000nm, Solid Lipid Nanoparticles (SLNs) combine the benefits of liposomes, emulsions, and other colloidal systems to deliver drugs at their targets. Objective: Aim and objective of the present work is to formulate wheatgrass extract loaded solid lipid nanoparticles using Central Composite design and to investigate the effect of formulation variables. Using hot homoginization method, the present work aimed to formulate wheatgrass loaded chitosan solid lipid nanoparticles using central composite design and to evaluate the extract potential to treat breast cancer on MCF-7 cell line. Methods: This study investigated the effect of three formulation variables on particle size, namely the sodium alginate concentration, the calcium carbonate concentration, and the homogination time. Extraction of wheatgrass was done in soxhlet extractor, using methanolic extract. The hot homogenization technique was used to prepare Triticum aestivum extract loaded solid lipid nanoparticles (SLNs). Result: For CCD, all formulations were analyzed for particle size, which ranged from 362.5 to 933.8 nm, and for polydispersity index, which ranged from 0.137 to 5.799. Batch code SLN-6 was found to be finest suitable because of maximum loading capacity of 67.76 ±0.17 % (w/w), maximum entrapment efficiency of 65.81 ± 0.11% (w/w) and minimum particle size of 362.5nm by using sodium alginate as surface stabilizer at homogenization time 5 min and having maximum percentage yield of 43.66%. Conclusion: During characterization studies and MCF-6 cell line studies, it was found that batch code SLN-6 was found to be finest suitable and wheatgrass has anti-oxidant potential, and potent against breast cancer.
Keywords: Solid lipid nanoparticles